Penerapan Model Pembelajaran Guided Inquiry Untuk Meningkatkan Keterampilan Komunikasi Siswa Kelas VII SMP Negeri 14 Lubuklinggau - Diana; Tri Ariani; Endang Lovisa (Prosiding Silampari Conference of Life Sciences and Techonology (Silamparilist), 2026)
This study aims to determine the improvement in communication skills among 7th-grade students at SMP Negeri 14 Lubuklinggau through the implementation of the Guided Inquiry learning model within the topic of Motion and Force. A quantitative research method was employed, utilizing a pre-experimental design—specifically, the One-Group Pretest-Posttest Design. The research subjects consisted of 30 students from class VII.1, selected via simple random sampling from a total population of 156 7th-grade students. Data on communication skills were collected using an observation sheet covering five indicators: listening and showing respect, self-confidence, effectively conveying ideas, taking responsibility for ideas, and communicating effectively. Data analysis was conducted using descriptive percentage analysis. The results indicate a gradual improvement in students' communication skills: the average score rose from 63.33% in the first meeting to 83.33% in the second, reaching 85.00% in the third, ultimately placing the students in the "good" qualification category. These findings demonstrate that the Guided Inquiry learning model is effective for fostering and enhancing students' communication skills in Physics-based Science learning.